2019
DOI: 10.1136/bmjsrh-2019-200375
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and sexual factors associated with recent sexual health clinic attendance and HIV testing among trans people in the UK

Abstract: ObjectivesTrans people remain an understudied population in the UK, with unmet sexual health needs. The aim of this research was to identify possible barriers and facilitators for sexual health clinic attendance and HIV testing among trans people.MethodsLesbian, gay, bisexual and transgender (LGBT) participants from across the UK were invited to take part in a cross-sectional online survey through Facebook advertising (April–June 2018). Psychosocial and sexual factors associated with recent sexual health clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…The primacy of these issues suggest generic HIV testing services are neither accessible nor appropriately tailored for trans people in England and Wales, including those services that advertise as LGBT inclusive. These findings are consistent with research from the UK and other settings [ 5 , [7] , [8] , [9] , [10] ]. It should be noted that services designed specifically for trans people were very highly valued.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The primacy of these issues suggest generic HIV testing services are neither accessible nor appropriately tailored for trans people in England and Wales, including those services that advertise as LGBT inclusive. These findings are consistent with research from the UK and other settings [ 5 , [7] , [8] , [9] , [10] ]. It should be noted that services designed specifically for trans people were very highly valued.…”
Section: Discussionsupporting
confidence: 91%
“…Trans women are also disproportionately represented in sex work, leading to additional sexual health needs which may be poorly met by existing services [11]. HIV testing rates among trans people in the UK are sub-optimal, with 49% of 500 trans participants reporting no lifetime HIV testing in a recent study [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst ve trials of YMSM were identi ed, none were found that focused on other LGBTQI + groups. There is a notable dearth of interventions for this group (excluding YMSM/MSM), particularly for trans youth (64).…”
Section: Discussionmentioning
confidence: 99%